IMPLICATURE ANALYSIS IN PIRATES OF CARIBBEAN: DEAD MEN TELL NO TALES MOVIE (Sastra Inggris UNPAM, 2022)
The purposes of this study are to identify types of implicature and identify the meaning found in Pirates of Caribbean: Dead Men Tell No Tales Movie. The writer used Grice (1975) theory of implicature and the classification, conversational and conventional implicature. Moreover, the writer used qualitative method to collect the data which are analyzed by using Grice theory. This study identifies the implicature used by the 8 casts. From the data analysis, it was found that there are 30 implicatures, there are 27 conversational and 3 conventional implicature. This study found more data from conversational implicature because 27 conversations are depending on the context of the conversation or meant by the speaker's utterance that is not part of what is explicitly stated, while 3 conversations that used conjunction implicates of what is being said conventionally or someone’s utterance that could change at another time.Keywords: Implicature, Pirates of Carribean, Types of Implicature